PENERAPAN LEAN MANUFACTURING UNTUK MENINGKATKAN PRODUKTIVITAS SISTEM PRODUKSI DI PT. Z - Almira Zerlina Sri H.; Amelia Santoso; Yenny Sari (CALYPTRA, 2018)
PT. Z is a cocoa powder manufacturer that located in Sidoarjo, East Java. The factory wanted to implement the concept of Lean Manufacturing to overcome their problems such as, production loss and powder (scrap) which was spreading over their production floor and warehouse. This factory could improve their production system’s productivity with the deployment of Lean Manufacturing concept. Percentage of scraps and losses for initial condition is about 0,076% and 1,987%. Cycle time for grinding process and mixing process for initial concept is about 3,49 hours/ton and 14,2 hours/5ton. Process Cycle Efficiency (PCE) for the initial condition is 81%. After implementing the improvement initiatives, there were some differences on the indicators. Percentage of scraps and losses for the new condition was about 0,054% and 1,542%. Process Cycle Efficiency (PCE) was increased and becoming 82% with cycle time for grinding process is 2,7 hours/ton and 11,86 hours/5ton for mixing process.